Cross‐Coupling of α‐Carbonyl Sulfoxonium Ylides with C−H Bonds. Issue 42 (14th September 2017) - Barday, Manuel; Janot, Christopher; Halcovitch, Nathan R.; Muir, James; Aïssa, Christophe
Abstract: The functionalization of carbon–hydrogen bonds in non‐nucleophilic substrates using α‐carbonyl sulfoxonium ylides has not been so far investigated, despite the potential safety advantages that such reagents would provide over either diazo compounds or their in situ precursors. Described herein are the cross‐coupling reactions of sulfoxonium ylides with C(sp 2 )−H bonds of arenes and heteroarenes in the presence of a rhodium catalyst. The reaction proceeds by a succession of C−H activation, migratory insertion of the ylide into the carbon–metal bond, and protodemetalation, the last step being turnover‐limiting. The method is applied to the synthesis of benz[c]acridines when allied to an iridium‐catalyzed dehydrative cyclization. Abstract : A new alliance : The rhodium‐catalyzed cross‐coupling of sulfoxonium ylides with carbon–hydrogen bonds, in hexafluoroisopropanol at 60–90 °C, brings these reagents into the realm of C−H activation. When allied to an iridium‐catalyzed dehydrative cyclization, this cross‐coupling streamlines the synthesis of valuable heterocycles.